1981
DOI: 10.1002/cm.970010303
|View full text |Cite
|
Sign up to set email alerts
|

Video‐enhanced contrast, differential interference contrast (AVEC‐DIC) microscopy: A new method capable of analyzing microtubule‐related motility in the reticulopodial network of allogromia laticollaris

Abstract: A new method called Allen Video-enhanced Contrast, Differential Interference Contrast (AVEC-DIC) microscopy is shown to be sufficiently sensitive to detect several new features of microtubule-related motility in the reticulopodial network of the foraminifer, Allogromia. The method takes advantage of the variable gain and offset features of a binary video camera to operate the DIC microscope under conditions highly favorable for video imaging, but in which the optical image is virtually invisible to the eye yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(147 citation statements)
references
References 12 publications
1
145
0
1
Order By: Relevance
“…The movement of axoplasmic organelles on nucleated skeletal muscle actin filaments or endogenous neuronal actin filaments was observed by AVEC-DIC microscopy (Allen et al, 1981Weiss et al, 1989) and video intensified fluorescence microscopy (Weiss et al, 1989). A Zeiss Axiophot microscope (C. Zeiss, Inc., Thornwood, NY) equipped with oil immersion condenser (NA 1.4) and ×100 DIC Plan Neofluar oil objective (NA 1.32) were used.…”
Section: Avec-dic and Fluorescence Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The movement of axoplasmic organelles on nucleated skeletal muscle actin filaments or endogenous neuronal actin filaments was observed by AVEC-DIC microscopy (Allen et al, 1981Weiss et al, 1989) and video intensified fluorescence microscopy (Weiss et al, 1989). A Zeiss Axiophot microscope (C. Zeiss, Inc., Thornwood, NY) equipped with oil immersion condenser (NA 1.4) and ×100 DIC Plan Neofluar oil objective (NA 1.32) were used.…”
Section: Avec-dic and Fluorescence Microscopymentioning
confidence: 99%
“…A Hamamatsu C2400-07 Newvicon camera was used to acquire DIC images and a Hamamatsu C2400-97 intensified CCD camera system (Hamamatsu Photonics, Inc., Bridgewater, NJ) for fluorescence images. The video signals were first subjected to analog contrast enhancement (Allen et al, 1981Weiss et al, 1989), followed by real-time digital image processing in the following steps: subtraction of an out-of-focus background (mottle pattern), accumulation or averaging of images to increase signal to noise ratio, and finally selection of the desired range of gray levels (Allen and Allen, 1983;Inoué, 1986;Weiss and Maile, 1993). The analog and digital processing of fluorescence and DIC signals was performed in parallel using two ARGUS 10 real time image processors (Hamamatsu Photonics Inc.).…”
Section: Avec-dic and Fluorescence Microscopymentioning
confidence: 99%
“…The development of optical and video methods for visualizing individual MTs in cell-free systems (2,29) has led to the discovery and characterization of several motor enzymes that move over a MT surface: kinesin, which generally moves over MTs in vitro toward their plus ends (86)(87)(88)(89), and cytoplasmic dynein, which usually moves in the opposite direction (37,64, and reviewed in reference 45) . More recently, however, members of the kinesin family have been found that move in the same direction as dynein (42,93, and reviewed in reference 11), and a dynein-like protein seems capable of moving in either direction (81) .…”
Section: The Generation Ofmitotic Forcesmentioning
confidence: 99%
“…Video-enhanced DIC allows enchantment of contrast while removing unwanted background signal (such as fixed image noise due to dust particles, non-uniform illumination or other imperfections in the optical system) by subtraction of a reference image with no specimen 5 . Also S. Inoué and R.D.…”
Section: Introductionmentioning
confidence: 99%